A novel frameshift mutation of COL4A5 in a Chinese family with presumed IgA nephropathy and chronic glomerulonephritis. Issue 12 (6th September 2020) - Zhu, Qian; Zhou, Cong; Wang, Jing
Abstract: Background: Alport syndrome (ATS) is a hereditary nephritis with hereditary and clinical heterogeneity; the early clinical symptoms are atypical, which can easily lead to misdiagnosis. The proband, a 6‐year‐old girl, was found to have microscopic hematuria, proteinuria, and visual impairment at about 5 years old; the results of renal pathological examination revealed mesangial hyperplasia and IgA deposition. The proband's father exhibited gross hematuria, eye swelling, and bilateral hearing loss after the age of 5, renal function progressively decreased, and he underwent right renal allograft at the age of 23 due to renal failure. The proband and her father were clinically diagnosed as IgA nephropathy and chronic glomerulonephritis, respectively. Methods: For proband, targeted exome capture sequencing was performed using the Targeted Exome Capture Kit; this kit targets 162 genes known to cause renal diseases. The identified mutation was confirmed and analyzed for cosegregation by Sanger sequencing in other family members whose gDNA was available. Results: Targeted exome capture sequencing revealed a novel heterozygous variant (NM_000495, c.697delG, p.G233fs) in the COL4A5 gene of the proband; the variant was inherited from her father. The variant was likely pathogenic according to the criteria of the American College of Medical Genetics and Genomics. Conclusion: In this study, we first report a c.697delG mutation of COL4A5 in two patients presumed IgA nephropathy and chronic glomerulonephritis. This study emphasizes on the diagnostic value of next‐generation sequencing for hereditary kidney diseases to help in their timely and cost‐effective diagnosis, determine appropriate treatments, and promote genetic counseling.